Exploration of the Relationship between Age of Marriage and Income on the Level of Child Stunting in Tasikmalaya City - Firmadi, Sidik; Sarofah, Riska; Ramdhani, Hilal (Journal Public Policy, 2024)
This study specifically aims to examine the impact of income and age of marriage on the prevalence of stunting. The use of these two variables is associated with the influence of poor family income on inadequate family purchasing power to meet the needs of their children, as well as individual immaturity in terms of their mental readiness to marry. This study uses a mixed methods approach that integrates quantitative and qualitative research methodologies. This study was conducted in Bungursari District, specifically in three health centers: Bungursari Health Center, Sukalaksana Health Center, and Bantar Health Center. The research methodology used is a convergent parallel design. The findings of the study indicate a favorable correlation between income and child stunting in Tasikmalaya City. The findings of this study were proven by comprehensive interviews, which revealed a negative correlation between parental income and the amount of time spent with children. As a result, this dynamic gives rise to unfavorable parenting practices, while the age at which individuals marry does not have a favorable impact on child stunting. The findings of this study can be valuable information for those involved in addressing and reducing the problem of stunting in Tasikmalaya City.